Adjustment unit price for R.C.C works in foundation with water proofing admixture - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding adjustment unit price for R.C.C works in foundation with water proofing admixture of BRAC University new campus project.